China: Will they buy or sell? - Ehui, Simeon K.; Hertel, Thomas W.; Rae, A.; Nin-Pratt, Alejandro (2000)
China's future role in international agricultural trade continues to be a puzzle. Part of this puzzle, namely that related to grains, has received far more attention than has livestock trade, which has been relatively neglected. China is a net exporter of livestock products, although over the last two decades imports have been increasing faster than exports. The Organization of Economic Cooperation and Development (OECD) projects that China will be a major net importer of poultry meat by 2005. In contrast, the International Food Policy Research Institute (IFPRI) projects increase in China's net exports of poultry meat in the coming decades. Resolving this controversy requires examination of the forces underpinning changes in consumption patterns in China, as well as the structural changes that have been occuring in China's livestock industry. This paper illustrates China's net exports in non-ruminant meat production and forecasts to 2005; China's future trade in livestock products; non-ruminant production in China; cumulative productivity growth rates of pigs and poultry for China; and confidence intervals for China's 2005 non-ruminant trade balance due to uncertain productivity. The paper also discusses rising demand for livestock products; increase in supply; output gains and increased productivity; and increase in China's imports.